Pilot Study of Mindfulness Training on the Self-Awareness of Motor Symptoms in Parkinson’s Disease – A Randomized Controlled Trial - Buchwitz, Timo Marcel; Maier, Franziska; Greuel, Andrea; Thieken, Franziska; Steidel, Kenan; Jakobs, Viktoria; Eggers, Carsten (Frontiers in Psychology, 2021)
Objective: This study aims to evaluate feasibility and effects of a newly developed mindfulness intervention tailored to specific needs of patients with Parkinson’s disease (PD). Background: The phenomenon of impaired self-awareness of motor symptoms (ISAm) in PD might be reduced by increasing patients’ mindfulness. A PD-specific mindfulness intervention has been developed and evaluated as a potential treatment option: IPSUM (“Insight into Parkinson’s Disease Symptoms by using Mindfulness”). Methods: IPSUM’s effectiveness is evaluated by comparing an intervention with a waitlist-control group. Applying a pre-post design, patients were assessed before, directly after and eight weeks after treatment. The primary outcome was the change in a quantitative ISAm score from baseline to post assessment. Secondary outcome measures were PD-related affective changes and neuropsychological test performance. Feasibility was evaluated via feedback forms. Results: In total, 30 non-depressed and non-demented PD patients were included (intervention: n = 14, waitlist-control: n = 16). ISAm score did not change significantly, but the training group showed greater performance in sustained attention and language tasks over time. Additional changes included greater mindfulness as well as less sleeping problems and anxiety. Cognitive disturbances, apathy and sleeping problems worsened only in the waitlist-control group. Patients’ feedback regarding the training concept and material was excellent. Conclusions: IPSUM has not been capable of reducing ISAm in PD patients, but appears to be a feasible and effective concept to, amongst others, support mental health in the mid-term. It has to be noted though that the study was stopped beforehand because of the SARS CoV-2 pandemic. The lack of findings might therefore be caused by a lack of statistical power. The need for further research to better understand the mechanisms of ISAm and its connection to mindfulness in PD is highlighted.